2011
DOI: 10.1177/1359104510387881
|View full text |Cite
|
Sign up to set email alerts
|

Translation and standardization of the HoNOSCA (Health of the Nation Outcome Scales for Children and Adolescents) scale in a Greek sample

Abstract: The Health of the Nation Outcome Scales for Children and Adolescents (HoNOSCA) is a brief measure of outcomes. Evidence for the effectiveness of patient treatments conducted in mental health services is limited in Greece. Thus, in an attempt to employ an easily administered and valid outcome measure, to assess outcomes in clinical practice for children and adolescents, but also to be able to compare the results across countries, the HoNOSCA was the measure of choice. In this study we have translated and valida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Our findings on the clinician version showed poor internal consistency (.58), which was similar to other studies that found low alpha at .45 [ 36 ] and .65 [ 37 ]. Inter-rater reliability for both scales was found to be strong and similar to those found in other studies, which range from 0.72 to 0.96 [ 17 , 18 , 27 29 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our findings on the clinician version showed poor internal consistency (.58), which was similar to other studies that found low alpha at .45 [ 36 ] and .65 [ 37 ]. Inter-rater reliability for both scales was found to be strong and similar to those found in other studies, which range from 0.72 to 0.96 [ 17 , 18 , 27 29 ].…”
Section: Discussionsupporting
confidence: 87%
“…Although few studies have reported on the self-report version of the HoNOSCA [ 16 , 17 ], the clinician rated version has been used extensively to regularly monitor the patient’s progress [ 13 ]. The HoNOSCA has four subscales relating to: (i) a behaviour (disruptive behaviour, overactivity, self-injury, inattention and substance misuse); (ii) an impairment (physical illness and disability - problems with scholastic or language skills, physical illness or disability problems); (iii) symptoms (psychotic and emotional symptoms - problems associated with hallucinations, delusions or abnormal perceptions, problems with non-organic somatic symptoms or emotional and related symptoms); and (iv) a social ((problems with peer, family relationships, problems with self-care and independence, poor school attendance) [ 17 , 18 ]. Several studies have examined the psychometric properties of the HoNOSCA [ 13 , 14 , 16 ] and because of its good psychometric properties and ease of use in routine clinical services, it has been translated into different languages [ 18 ].…”
Section: Introductionmentioning
confidence: 99%